Ołtarz Zbigniewa Herberta - wiersz, styl, semantyka - Bodusz, Marek (Wydawnictwo Naukowe UAM, 2008)
In this text I present the poem by Zbigniew Herbert "Ołtarz" as a text whose style and line structure refer to "Bema pamięci żałobny rapsod" by Cyprian Kamil Norwid. The poem from 19th century puts a special meaning as "the most outstanding realisation of Polish hexameter" to contemporary works. The hexameter that comes from ancient tradition (Homer) evokes associations connected with it: seriousness, pathos and also the distance to described events. Using the hexameter is an important clue of an author who gives information about understanding of innate "I" expression on the level of style, rhythm and line structure of a poem ("a gesture" of restriation to regular form). Such poetic strategy gives Herbert a possibility of expressing his pessimistic and ironic opinions about art - "self-possessed poet" has a possibility of artistic object description which is not “a monument impossible to be destroyed", on the contrary - it is an object that is under the destructive power of time.
"Ołtarz" by Zbigniew Herbert - line structure, style, semantics